Risk Factors for Gastrointestinal Cancer: a Study in General Surgery and Gastroenterology Patients - Iván Pimienta Concepción; Icler Naum Sisalema Aguilar; Diego Fernando Vaca Sánchez (Revista Finlay)
Foundation: gastrointestinal cancer is one of the main causes of morbidity and mortality worldwide. It refers to types of cancer that affect the organs of the digestive system. Objective: to evaluate the impact of risk factors that influence the development of cancer of the gastrointestinal tract and the need for health education in cancer prevention. Methods: an observational study was carried out in the General Surgery Department of a private hospital, with 50 patients hospitalized for cancer of the gastrointestinal tract, which included: stomach, pancreas and colorectal cancer. The sample corresponded to the population. A purpose-built questionnaire was used to collect sociodemographic information, hereditary and risk factors, and the patient's level of knowledge about gastrointestinal cancer. The selected data were processed using the SPSS v statistical program 23 for Windows. To evaluate the correlation between sociodemographic and hereditary variables and lifestyle habits with the patients' cancer types, the Chi-square test was performed. Results: the prevalence detected was in male patients between 60 and 69 years old. Most respondents indicated that there was no history of cancer in their immediate family. The most common symptoms of gastrointestinal cancer mentioned by respondents were weight loss, abdominal pain, and blood in the stool. Among the risk factors found, alcohol intake, gastritis due to helicobacter pylori and smoking prevail. Respondents rated their knowledge of gastrointestinal cancer risk factors as moderate. Conclusions: there is a need to disseminate information and promote awareness about gastrointestinal cancer in the population, its early detection and education about risk factors.